Primary histiocytic sarcoma breast, a very rare case report - Mulchandani, Nikita Jaiprakash; Mehta, Bhavana Asit; Parmar, Vipal Hasmukhbhai; Shah, Sandip Chandrakant; Murnal, Ankita Girish (Eastern Journal of Medical Sciences, 2024)
Histiocytic sarcoma (HS) is an uncommon, aggressively evolving histiocytic tumor showing macrophage differentiation. It is typically composed of non-cohesive large cells that show positive immunostaining for two or more histiocytic markers, are negative for T-cell, B-cell, myeloid cell, and follicular dendritic cell markers, and are also negative for CD1a and langerin. In this article, we present the case of a 49-year-old female who was diagnosed with mammary HS.